PERANCANGAN SISTEM INFORMASI PELAYANAN PADA MOGELLE CAFE - Sianturi, Nico Bangun Rezkyanto; Tukino, Tukino (Universitas Putera Batam, 2023)
The development of the café industry or similar restaurant service industries is increasingly popular among consumers in the city of Batam. Efforts to improve the services provided to all customers coming to Café are being carried out, including café mogelle, which is facing issues in the digitalization of café management services. The researchers used the waterfall development method to develop the service information system in the café and used UML diagrams to design the entire process that occurs in the café mogelle service information system. The results of this research show the proposed solution to café mogelle, which adds value that can be felt by consumers by improving services through the café mogelle service information system. This research has a positive impact on café owners or managers and enhances the productivity or performance of staff and cashiers. Through this café mogelle information system, payment and ordering processes can be carried out through the built system.